2017
DOI: 10.1017/s0033291717001957
|View full text |Cite
|
Sign up to set email alerts
|

Directed threat imagery in generalized anxiety disorder

Abstract: The present study presents the first behavioral and neural evidence for emotional reactivity during directed threat imagery in GAD. The brain activity pattern suggests an involvement of a fear processing network as a neural correlate of initial exposure during directed imagery in CBT in GAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…Previous neuroimaging studies have suggested that the thalamus plays an important role not only in the filtering of sensory information, but also involved in the process of senior cognition and emotion regulation ( Herrero et al, 2002 ; Boatman and Kim, 2006 ; Haber and Calzavara, 2009 ). Previous findings indicate elevated activity in the thalamus in GAD patients relative to HC during directed threat imagery ( Buff et al, 2017 ). Furthermore, increased connectivity between amygdala and thalamus was predicted by the amplified physiological responses to the induction ( Makovac et al, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous neuroimaging studies have suggested that the thalamus plays an important role not only in the filtering of sensory information, but also involved in the process of senior cognition and emotion regulation ( Herrero et al, 2002 ; Boatman and Kim, 2006 ; Haber and Calzavara, 2009 ). Previous findings indicate elevated activity in the thalamus in GAD patients relative to HC during directed threat imagery ( Buff et al, 2017 ). Furthermore, increased connectivity between amygdala and thalamus was predicted by the amplified physiological responses to the induction ( Makovac et al, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
“…The GAD is highly prevalent in the general population. Patients with GAD often suffer from a variety of anxiety-related physical symptoms like difficulty concentrating, irritability, muscle tension, and disturbed sleep which impair their quality of life and social functioning ( Paulus and Stein, 2010 ; Liu et al, 2015b ; Li Y. et al, 2016 ; Buff et al, 2017 ; Moon and Jeong, 2017 ). To improve the level of both basic GAD research and its clinical diagnosis, it is essential to understand the pathophysiological mechanisms of GAD and explore a valid and objective biomarker to distinguish patients with GAD from HC.…”
Section: Introductionmentioning
confidence: 99%
“…It has connections with widespread cortical and subcortical regions (Qiao et al, 2017) and participates in multiple cognitive and emotional processes (Jiang et al, 2018). Previous studies reported hyperactivation of the thalamus in GAD during imagining disorder-related scenarios (Buff et al, 2018), and increased rsFCs of the thalamus in GAD patients (Etkin et al, 2009;Qiao et al, 2017). Consistent with functional impairments, GAD also exhibits structural abnormalities in the limbic system, such as reduced gray matter volume in regions including the hippocampus, thalamus and insula (Abdallah et al, 2013;Moon, Kim, & Jeong, 2014;Moon, Yang, & Jeong, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…PFC, ACC and amygdala were all reported to act abnormally in GAD, as indicated above. Insula and hippocampus were also included because both insula and hippocampus have been found to be implicated in GAD’s pathology as well 1 [ 1 , 33 , 34 ]. What’s more, all of these brain regions are considered as part of emotion circuitry [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Firstly, hippocampus is considered part of the limbic system responsible for fear generation and was part of common neurocircuitry implicated in all anxiety disorders [ 1 ]; secondly, connectivity between insula and amygdala was impaired in GAD patients [ 9 , 33 ]; thirdly, both insula and hippocampus showed increased activation under emotional task in GAD patients [ 34 ]. …”
mentioning
confidence: 99%